ANALISIS KINERJA BANK BCA SYARIAH BERDASARKAN METODE RGEC DAN ISLAMICITY PERFORMANCE INDEX - Rahmat Daim Harahap; Hendra Harmain; Hasna Hidayah Siahaan (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
This study aims to review the performance of Bank BCA Syariah through the method measurement that has beeb stipulated in Bank Indonesia Regulation Number 13/1/PBI/2011 concerning the bank soundness rating system using the RGEC and islamicity performace index method. Researcher data that used quantitative data derived from secondary data on financial statements in Bank BCA Syariah 2016-2019. The data analysis in this study resulted in the level of the health of BCA Syariah banks in 2016-2019 is ranked composite 1 in the “Very Healthy” category. This proves that the BCA bank Sharia is able to  face the influance of competition. Different, on the method islamicity performance index of BCA Syariah bank is in Good Enough condition it is clear from the ratio of zakat performance index and EDR net profit which is still in the poor category.